2017
DOI: 10.1021/acs.macromol.7b00192
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Oxygen Reduction for Dark Polymerization

Abstract: Photopolymerization systems for controlled/living radical polymerization (CLRP) have often been dependent on continuous irradiation to sustain radical production. Although this approach offers an opportunity to impose spatial and temporal control, it remains an energy inefficient process. As energy storage for CLRP remains an unexplored area in polymer chemistry, it may provide an opportunity for designing energy efficient polymerization. In this contribution, we propose a novel energy storage system where in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 118 publications
2
66
0
Order By: Relevance
“…[21][22][23] When we applied this system to flow polymerisations,the ZnTPP was able to perform two functions in the polymerisation when activated by visible light (at 560 nm); 1) converting triplet oxygen to singlet oxygen which is irreversibly trapped by the DMSO solvent, and 2) activating the RAFT agent to provide asource of initiation for the CRP. We recently reported an ew photoinduced RAFT (PET-RAFT) polymerization technique using zinc tetraphenylporphyrin (ZnTPP) as acatalyst, which can enable oxygen tolerant polymerisations in organic solvents such as DMSO.…”
mentioning
confidence: 99%
“…[21][22][23] When we applied this system to flow polymerisations,the ZnTPP was able to perform two functions in the polymerisation when activated by visible light (at 560 nm); 1) converting triplet oxygen to singlet oxygen which is irreversibly trapped by the DMSO solvent, and 2) activating the RAFT agent to provide asource of initiation for the CRP. We recently reported an ew photoinduced RAFT (PET-RAFT) polymerization technique using zinc tetraphenylporphyrin (ZnTPP) as acatalyst, which can enable oxygen tolerant polymerisations in organic solvents such as DMSO.…”
mentioning
confidence: 99%
“…The peroxide degrades into hydroxyl radicals, which initiated the polymerizations and resulted in conversions up to 80% with no further irradiation. Further investigation found that conversion was indeed proportional to the amount of air present in the system at reaction start, and reinitiation by addition of air and several minutes of irradiation was also possible . This process is shown in Scheme .…”
Section: Aqueous Photoatrp and Photoraftmentioning
confidence: 87%
“…Proposed mechanism of dark‐driven photopolymerization by storing of photochemical energy. Adapted with permission . Copyright 2017, American Chemical Society.…”
Section: Mechanistic Considerations In Photochemically Driven Raftmentioning
confidence: 99%
See 1 more Smart Citation
“…They utilized the so‐called Fenton reaction, i.e., the cleavage of hydrogen peroxide into a hydroxo anion and a hydroxyl radical in the presence of Fe 2+ ions, for initiating ultrafast and well‐controlled RAFT polymerizations of acrylamides and acrylates. Moreover, Boyer and co‐workers investigated the photo‐organocatalyst eosin Y in combination with ascorbic acid to reduce oxygen to hydrogen peroxide and subsequently generate initiating hydroxyl radicals . In addition, enzymes can be utilized to in situ produce hydrogen peroxide from oxygen .…”
Section: Introductionmentioning
confidence: 99%